The Antiseptic Octenidine Inhibits Langerhans Cell Activation and Modulates Cytokine Expression upon Superficial Wounding with Tape Stripping - Nenad Nikolić; Philip Kienzl; Pooja Tajpara; Martin Vierhapper; Johannes Matiasek; Adelheid Elbe-Bürger (Journal of Immunology Research)
Ideal agents for the topical treatment of skin wounds should have antimicrobial efficacy without negative influence on wound healing. Octenidine (OCT) has become a widely used antiseptic in professional wound care, but its influence on several components of the wound healing process remains unclear. In the present study, we have used a superficial wound model using tape stripping on human full-thickness skin ex vivo to investigate the influence of OCT on epidermal Langerhans cells (LCs) and cytokine secretion pattern of skin cells during wound healing in a model without disruption of the normal skin structure. Histological and immunofluorescence studies showed that OCT neither altered human skin architecture nor the viability of skin cells upon 48 hours of culture in unwounded or wounded skin. The epidermis of explants and LCs remained morphologically intact throughout the whole culture period upon OCT treatment. OCT inhibited the upregulation of the maturation marker CD83 on LCs and prevented their emigration in wounded skin. Furthermore, OCT reduced both pro- and anti-inflammatory mediators (IL-8, IL-33, and IL-10), while angiogenesis and growth factor mediators (VEGF and TGF-β1) remained unchanged in skin explant cultures. Our data provide novel insights into the host response to OCT in the biologically relevant environment of viable human (wounded) skin.